Copper catalysis at operando conditions—bridging the gap between single nanoparticle probing and catalyst-bed-averaging - David Albinsson (Nature Portfolio, 2020)
Characterizing individual catalyst nanoparticles at operando conditions is a cornerstone of catalysis research. Here the authors utilize plasmonic optical nanoimaging in a nanofluidic reactor to map the impact of reactor geometry on single Cu particle oxidation state dynamics and active phase during CO oxidation.